Kelayakan Objek Wisata Alam Gua Pengkoak di Taman Hutan Raya Nuraksa - Firashinta, Aminah; Aji, Irwan Mahakam Lesmono; Anwar, Hairil (Jurnal Wana Tropika, 2022)
Natural tourism is one type of the tourism that contributes to regional income. The natural tourism object of Pengkoak Cave is one of the tourist destinations located In Forest Park (Tahura) Nuraksa. Tourism activities have long existed in this natural tourism object of Pengkoak Cave, lack of research has been done therefore its feasibility has not been tested. In its management, tourism requires tested feasibility standards in order for tourism to remains sustainable. This research was carried out to understand the feasibility of the natural tourism object of Pengkoak Cave. This research refers to the National Standardization Agency (2014), that is the principle of natural tourism management of the Indonesian National Standard (SNI) which includes the preservation of ecosystem functions, preservation of natural tourist attraction objects (ODTWA), socio-cultural sustainability, visitors satisfaction, safety and comfort, and economic benefits. The result show that the natural tourism object of Pengkoak Cave obtains feasibility value of 93% which falls in the category of eligible (feasibility value >66.6%) based on the ADO-ODTWA criteria. Keywords; Feasibility Analysis; Natural Tourism; Pengkoak Cave